Home » Aptitude » Algebra » Question
  1. The simplest form of the expression
    ( p² - p )
    ÷
    ( p² - 1 )
    ÷
    is
    2p³ + 6p²p² + 3pp + 1
    1. 2p²
    2. 1
      2p²

    3. p + 3
    4. 1
      p + 3
Correct Option: B

Expression =
( p² - p )
÷
( p² - 1 )
÷
2p³ + 6p²p² + 3pp + 1

Expression =
p( p - 1 )
÷
( p + 1 )( p - 1 )
÷
2p²( p + 3 )p( p + 3 )( p + 1 )

Expression =
p( p - 1 )
×
p( p + 3 )
×
( p + 1 )
2p²( p + 3 )( p + 1 )( p - 1 )

Expression =
1
2p²



Your comments will be displayed only after manual approval.